2014
DOI: 10.1007/s13197-014-1503-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of selenium-enriched wheat by agronomic biofortification

Abstract: Agronomic biofortification of staple crops is an effective way to enhance their contents in essential nutrients up the food chain, with a view to correcting for their deficiencies in animal or human status. Selenium (Se) is one such case, for its uneven distribution in the continental crust and, therefore, in agricultural lands easily translates into substantial variation in nutritional intakes. Cereals are far from being the main sources of Se on a content basis, but they are likely the major contributors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 63 publications
4
47
2
1
Order By: Relevance
“…Studies showed that foliar Se spray can increase the Se concentration in grain crops. For example, the Se concentration was approximately 2000 µg kg −1 in wheat grains after spraying foliar Se at 100 g ha −1 , 410 µg kg −1 in the rice grains after spraying foliar Se at 75 g ha −1 , and 1627–1827 µg kg −1 in the maize grains after spraying foliar Se at 200 g ha −1 . In the present study, the Se concentration of blueberry was only 44–114 µg kg −1 after spraying foliar Se spray at 200 g ha −1 and the Se‐enrichment ability of maize was approximately 14‐ to 42‐fold higher than that of the blueberry.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Studies showed that foliar Se spray can increase the Se concentration in grain crops. For example, the Se concentration was approximately 2000 µg kg −1 in wheat grains after spraying foliar Se at 100 g ha −1 , 410 µg kg −1 in the rice grains after spraying foliar Se at 75 g ha −1 , and 1627–1827 µg kg −1 in the maize grains after spraying foliar Se at 200 g ha −1 . In the present study, the Se concentration of blueberry was only 44–114 µg kg −1 after spraying foliar Se spray at 200 g ha −1 and the Se‐enrichment ability of maize was approximately 14‐ to 42‐fold higher than that of the blueberry.…”
Section: Discussioncontrasting
confidence: 38%
“…The low bioavailability of Se fertilizers applied to the soil is the result of some natural factors, such as soil type, redox condition, microbial activity and rainfall . Galinha et al . found that the Se concentration for foliar Se spray is two‐fold higher than that of soil Se application in wheat grains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenite and selenate are the inorganic forms of water‐soluble Se and are the most bioavailable forms of the element for plants (Dungan and Frankenberger, 1999). However, several studies have shown that selenate accumulates more in plant tissues than does selenite (Poblaciones et al, 2014; Galinha et al, 2015), due to the higher transportation rate of selenate through the xylem (Gupta and Gupta, 2017).…”
mentioning
confidence: 99%
“…The awareness that the intake of Se by plants is the first step of Se entry into the human food chain could explain why biofortification with this element has received great attention. For instance, field treatments with Se or Se-rich compounds can be considered a safe, low-cost approach to achieving biofortification in Se-deficient areas [2,4,13,20,25,32,33].…”
Section: Introductionmentioning
confidence: 99%